THE POTENCY OF SUMBA ONGOLE (SO) CATTLE: A STUDY OF GENETIC CHARACTERIZATION AND CARCASS PRODUCTIVITY - Agung, P. P.; Anwar, S.; Wulandari, A. S.; Sudiro, A.; Said, S.; Tappa, B. (Journal of the Indonesian Tropical Animal Agriculture, 2015)
A study was conducted to assess the genetic characterization of the Sumba Ongole (SO) cattlebased on DNA microsatellites and also to study the potency of SO cattle based on carcass productivity.Blood samples were collected from 28 individual cattle and 12 microsatellite primers as recommendedby FAO were used to identify the genetic characterization of the SO cattle population. Data of carcassproductivity were collected from 506 individual cattle that slaughtered in Karawaci abattoir, Banten,Indonesia. The heterozygosity values of microsatellite loci ranged from 0.143 to 1.000 (mean 0.536).The highest PIC values was 0.814 (locus TGLA122), while the lowest was 0.280 (locus BM1818).Cattle in range of 351-475 kg slaughter weight was most slaughtered in year 2013 and 2014 with carcasspercentage ranged from 52.89% to 53.43%. The highest carcass percentage (56.34%) was obtained fromcattle in range of 626-650 kg slaughter weight while the lowest (51.42%) was obtained from cattle inrange of 250-275 kg slaughter weight. The results of genetic characterization showed that allmicrosatellite locus were highly polymorphic and highly informative for detecting the level of geneticdiversity in the SO cattle population. The results of carcass productivity showed that the SO cattle hasexcellent potential as beef cattle compare with other local breeds cattle in Indonesia.